THE CORRELATION AMONG SELF-CONCEPT, READING ATTITUDE, AND THE NINTH GRADE STUDENTS’ READING COMPREHENSION OF STATE JUNIOR HIGH SCHOOL 51 PALEMBANG - Riza Yulianti (Universitas PGRI Palembang, 2021)
This research aims to determine the relationship between self-concept, reading attitudes, and reading comprehension of the ninth grade students of SMPN 51 Palembang. In this study 30 ninth grade students were selected as a stratified random sample. and tests are used to collect data. The analysis was performed using the Pearson product moment correlation coefficient, Normality Test, Homogeneity Test, Linearity Test and multiple regression. The results showed that the correlation coefficient between self concept showed the level of significant was 0.000 <0.05. showed the level of significant was 0.000 <0.05. The correlation coefficient between self concept showed the level of significant was 0.000 <0.05. The correlation coefficient between self concept showed the level of significant was 0.000 <0.05.